THE EFFECTIVENESS OF VARIABLE PEDAGOGICAL APPROACHES IN DEVELOPING VALEOLOGICAL CULTURE AMONG STUDENTS IN GRADES 5–9 (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the effectiveness of variable pedagogical approaches in developing valeological culture among students in grades 5–9. Valeological culture is interpreted as an integrated system of knowledge, values, attitudes, and practical skills related to health preservation, healthy lifestyle behavior, personal hygiene, physical activity, emotional self-regulation, and responsible decision-making. The study is grounded in the idea that middle school students differ in age-related development, learning needs, motivation, social environment, and health-related behavior patterns; therefore, a uniform instructional model cannot ensure stable educational outcomes. A variable pedagogical approach makes it possible to adapt content, methods, forms of instruction, and educational support to students’ individual and group characteristics. The article analyzes the pedagogical potential of differentiated instruction, interactive learning, health-oriented educational tasks, cooperative activities, and reflexive practices in strengthening students’ valeological awareness and behavior. The findings emphasize that a flexible and learner-centered educational environment improves students’ engagement, promotes sustainable health values, and increases the practical effectiveness of valeological education in school settings.
Keywords: Valeological culture, variable pedagogical approach, health education, middle school students, healthy lifestyle, learner-centered instruction, physical education, pedagogical effectiveness.